Lingual Markers in Da'wah Messages in a Movie Entitled Ustad Millennial - Laili Etika Rahmawati; Ristika Dwi Pramutya (Faculty of Da'wah and Communication, UIN Sunan Gunung Djati, Bandung, 2022)
The purpose of this study is to describe the form of lingual markers and da'wah messages that exist in the dialogue of the film